Karakteristik Morfoanatomi Limnobium laevigatum (Amazon Frogbit) dan Potensinya sebagai Tumbuhan Invasif di Perairan Rawa Pangkalan Bun - Rini Pamundhi Bekti; Alif Afri Diyana Dewi; Sascia Rahma Putri (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Limnobium laevigatum is a non-native aquatic plant with invasive potential due to its high adaptability and rapid growth in swamp waters, which may disrupt habitat balance. This study aimed to describe the morphological and anatomical characteristics of Limnobium laevigatum and to analyze its potential as an invasive aquatic plant in the swamp waters of Baru Village, Pangkalan Bun, Indonesia. The study was conducted from April to May 2026 using a qualitative descriptive method. A total of 14 specimens were collected directly from the study site and subsequently selected based on intact morphological characteristics, including complete leaves, petioles, and roots without visible damage. Eight selected specimens that met these criteria were used for morphological observations and anatomical preparations at the Fisheries Production Laboratory, Faculty of Agriculture, Animal Husbandry, and Fisheries Ecology, Universitas Antakusuma. The results showed that Limnobium laevigatum possesses floating rosette-shaped leaves with smooth green surfaces, a freely hanging fibrous root system, and reproduces through both vegetative and generative propagation. Anatomical observations revealed the presence of aerenchyma tissue in the petioles and leaves, which facilitates gas exchange and provides buoyancy. In addition, parenchyma tissue and vascular bundles support the transport of water and nutrients. These morphoanatomical characteristics indicate a capacity for adaptation to swamp environments, promoting rapid growth and dispersal. Therefore, Limnobium laevigatum has the potential to become an invasive aquatic plant in swamp ecosystems.